2010
DOI: 10.1016/j.ijpara.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of annexin A2 in cholangiocarcinoma caused by Opisthorchis viverrini and its implication as a prognostic marker

Abstract: Cholangiocarcinoma (CCA), or cancer of the bile ducts, is primarily associated with infection with the liver fluke Opisthorchis viverrini in northeast Thailand. The disease . is associated with late presentation, poses challenges for diagnosis and has a high mortality rate – features that highlight the need for tumor markers. At present, there are no specific tumor markers that can indicate the early stages and status of CCA. Proteomic analysis of the proteins expressed on the surface of tumor cells is particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 31 publications
4
25
0
1
Order By: Relevance
“…Compelling evidence from the literature suggests that annexin II may be a potential target for the development of effective therapeutic strategies for the treatment of cancer and its metastasis (Sharma and Sharma 2007). It was reported that Anxa2 protein was up-regulated in the tissues of OV-associated CCA patients and the up-regulation was correlated with the tumor progression stages and survivals (Yonglitthipagon et al 2010). Our results further confirmed the up-regulated expression in CCA, suggesting that Anxa2 can be a promising biomarker.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Compelling evidence from the literature suggests that annexin II may be a potential target for the development of effective therapeutic strategies for the treatment of cancer and its metastasis (Sharma and Sharma 2007). It was reported that Anxa2 protein was up-regulated in the tissues of OV-associated CCA patients and the up-regulation was correlated with the tumor progression stages and survivals (Yonglitthipagon et al 2010). Our results further confirmed the up-regulated expression in CCA, suggesting that Anxa2 can be a promising biomarker.…”
Section: Discussionsupporting
confidence: 82%
“…Some genes or signaling pathway have been found to be likely involved in the tumorigenesis or potential as biomarkers, for example, KRAS and TP53 (Tangkawattana et al 2008), RB1 signaling pathway genes (Boonmars et al 2009b), annexin A2, MMP-9 (Yonglitthipagon et al 2010), and IL-6 (Sripa et al 2009). However, most of these approaches used patient tissues that are usually in late stage of CCA.…”
Section: Introductionmentioning
confidence: 99%
“…In the cholangiocarcinoma cells, ANXA2 was upregulated. 21 Maxwell et al also studied ANXA2 associated with oxidative processes and inflammation in stage 1 endometrial cancer tissues based on proteomic analysis. 22 The expressions of ANXA2 also correlated with cervical cancer 23 and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics offers an unprecedented opportunity for identifying new biomarkers and therapeutic targets and providing an understanding of the biochemical pathways involved in pathogenesis (20). Using a shotgun proteomic approach, Kristiansen et al (25). In addition, these authors extended their analyses to include a computational analysis of the promoter regions of the proliferation-associated genes.…”
Section: Discussionmentioning
confidence: 99%